The Factors of Tourist Satisfaction Enhancement in Double-Decker Tour Bus - M Rifki Bakhtiar; Puji Setya Sunarka (Universitas Medan Area, 2020)
Research to analyze tourist satisfaction factors is the development of research on customer satisfaction which is designed based on tourist perceptions. Using double-decker buses as transportation that connects one destination to another gives tourists the experience of visiting a destination. Analysis of the influence of service quality, facilities, and destination image on tourist satisfaction is the aim of this study. The questionnaires that met the requirements of purposive sampling were 178 respondents. The data were processed by multiple linear regression analysis using SPSS 25. The results showed that all independent variables had a positive effect on tourist satisfaction. The factors that affect tourist satisfaction such as service quality, facilities, and destination image will contribute to the government in developing tourism, especially double-decker buses